Ulcers due to subcutaneous injection of medical ozone. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
Case report. A 24-year-old young man was first observed due to the presence of two ulcers on the lower third of the right leg. The young patient, who had been a keen sportsman as a weightlifter, reported Achilles' tendon bursitis approximately from 1 year, treated in various ways. The last therapy performed consisted of subcutaneous injections of medical ozone on both side surfaces of the Achilles' tendon, for a total of 8 sessions. Two days after the eighth injection the patient noticed two blackish crusts, which shrank in the following weeks and fell. On physical examination there were on the side surfaces of the Achilles' tendon two clear-cut ulcers on an erythematous background (Fig. 1). The Doppler ultrasound did not show significant alterations of the arterial and venous district, leading to the final diagnosis of vasospasm ulcers induced by subcutaneous injection of medical ozone. Three weeks later the ulcers healed with residual scar (Fig. 2).